2016
DOI: 10.1371/journal.pone.0152288
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Astaxanthin for the Treatment of Atopic Dermatitis in a Murine Model

Abstract: Atopic dermatitis (AD) is a common chronic inflammatory skin disease associated with various factors, including immunological abnormalities and exposure to allergens. Astaxanthin (AST) is a xanthophyll carotenoid that has recently been demonstrated to have anti-inflammatory effects and to regulate the expression of inflammatory cytokines. Thus, we investigated whether AST could improve the dermatitis and pruritus in a murine model of AD using NC/Nga mice. In addition to a behavioral evaluation, the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 34 publications
0
26
0
4
Order By: Relevance
“…In addition, treatment with astaxanthin prevented UV-induced DNA damage and apoptosis in vitro [ 30 , 37 ]. Furthermore, an earlier study showed the beneficial effects of astaxanthin for the treatment of atopic dermatitis [ 38 ]. Our study is in agreement with this report for the improvement of VAS regarding “improvement of rough skin” and “texture”.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, treatment with astaxanthin prevented UV-induced DNA damage and apoptosis in vitro [ 30 , 37 ]. Furthermore, an earlier study showed the beneficial effects of astaxanthin for the treatment of atopic dermatitis [ 38 ]. Our study is in agreement with this report for the improvement of VAS regarding “improvement of rough skin” and “texture”.…”
Section: Discussionmentioning
confidence: 99%
“…AST is well known as an excellent anti‐inflammatory agent that suppresses pro‐inflammatory cytokine and chemokine expression . Moreover, AST has been reported to have beneficial effects in allergic skin diseases such as AD and contact dermatitis . However, it has been only reported the inhibition effect of AST on pro‐inflammatory cytokine.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperproduction of total IgE level in skin lesions is typical clinical characteristics of AD . Chronic IgE‐dominated immune responses contribute to the damage of skin barrier causing the release of inflammatory mediators, which correlates with the severity of AD .…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous skin studies performed with astaxanthin using topical and oral applications that suggest: (a) prevention of DNA damage and enhanced mitochondrial function and DNA repair through its antioxidant and anti-inflammatory activities via the AKt pathway [ 67 , 69 ], (b) UV protection by decreasing oxidative stress presumably via the NF-κB dependent pathway [ 67 , 69 , 98 ], (c) immune-enhancing effects by increasing natural killer cell cytotoxic activity [ 99 , 100 ], (d) activation of the Nrf2 pathway, which stimulates the antioxidant defense system to produce more antioxidants [ 99 , 100 ], (e) inhibition of the matrix metalloproteinases (MMPs) that breakdown collagen and elastin [ 110 , 111 ], (f) stimulation of collagen type I and a basic fibroblast growth factor to improve the appearance of wrinkles and promote wound healing [ 111 , 112 , 113 , 114 , 115 , 116 , 117 ], and (g) improvement in TEWL, skin texture/smoothness, skin age spots, moisture content, and elasticity [ 118 , 119 , 120 , 121 , 122 ]. The main theme of astaxanthin’s dermal health influences centers around its powerful antioxidant effects [ 67 , 68 , 69 , 110 , 111 , 112 , 113 , 117 , 119 , 121 ].…”
Section: Astaxanthinmentioning
confidence: 99%